The Effect of Customer Satisfaction on La Sabelle Customer Loyalty in Palembang in The Period Of 2025 - Raihani, Adelia Tsafa (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
The purpose of this study is to analyze the influence of customer satisfaction on La Sabelle customer loyalty in Palembang both partially and simultaneously. The method in this study uses descriptive quantitative with 71 respondents loyal La Sabelle customers. The sampling technique uses nonprobability sampling with purposive sampling method and uses SPSS version 26. The results of this study indicate that the partial test (t test) customer satisfaction variables have a positive and significant effect on customer loyalty. Simultaneous test (F test) customer satisfaction variables have a positive and significant effect on customer loyalty.